Cure characteristics, mechanical, thermal, and coloring properties of natural rubber/dye‐loaded shell powder composites. Issue 4 (20th September 2017) - Zhou, Youzhou; Ge, Liuqin; Fan, Neng; Dai, Lingqing; Xia, Meisheng
ABSTRACT: To explore the application of shell powder (SP) in rubber, a dye‐loaded SP (DSP) bio‐filler based on SP and Congo red was incorporated into natural rubber (NR). The adsorption experiments demonstrated that the maximum monolayer adsorption capacity of Congo red onto SP was 69.3 mg/g. The effect of aluminate coupling agent and DSP was investigated by evaluating the cure characteristics, mechanical, thermal, and coloring properties of NR/DSP composites. It was suggested that the optimum amount of aluminate coupling agent was 2 wt %, and the best tensile strength (24.80 MPa) of vulcanizates was achieved at the DSP content of 20 phr, while other mechanical properties such as tear strength kept increasing with the addition of DSP. Furthermore, the improved thermal stability and uniform color distribution of the NR composites was obtained. The results indicate that DSP is promising to become a low‐cost filler and pigment for rubber materials. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 45750. Abstract :